2007
DOI: 10.1007/s00425-007-0503-5
|View full text |Cite
|
Sign up to set email alerts
|

11C-imaging: methyl jasmonate moves in both phloem and xylem, promotes transport of jasmonate, and of photoassimilate even after proton transport is decoupled

Abstract: The long-distance transport and actions of the phytohormone methyl jasmonate (MeJA) were investigated by using the short-lived positron-emitting isotope 11C to label both MeJA and photoassimilate, and compare their transport properties in the same tobacco plants (Nicotiana tabacum L.). There was strong evidence that MeJA moves in both phloem and xylem pathways, because MeJA was exported from the labeled region of a mature leaf in the direction of phloem flow, but it also moved into other parts of the same leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 54 publications
4
128
0
2
Order By: Relevance
“…Alternatively, they could serve as a source of cytokinin or signal the metabolic status of the plant . Jasmonic acid, an oxylipin moves through the phloem as part of the response to pathogen infection 22,29,31,32 . While the role of most phloem lipids is still unclear, some of them likely have signaling function 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, they could serve as a source of cytokinin or signal the metabolic status of the plant . Jasmonic acid, an oxylipin moves through the phloem as part of the response to pathogen infection 22,29,31,32 . While the role of most phloem lipids is still unclear, some of them likely have signaling function 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Wounded tissue rapidly activates JA biosynthesis (Glauser et al, 2008), and increased JA triggers the SKP1/Cullin/F-box E3 ubiquitin ligase complex containing the F-box subunit CORONATINE INSENSITIVE1 (SCF COI1 ) to degrade the repressors of JA signaling -the JASMONATE-ZIM (JAZ) family proteins -by the ubiquitin/26S-proteasome pathway (Chini et al, 2007;Thines et al, 2007). In addition to their local synthesis and action, JAs also move systemically via vascular strands to transmit wound signals to distal tissues (Li et al, 2002;Thorpe et al, 2007). Therefore, JAs can be considered to be good candidates for the mediator of wound-induced trichome formation, which is also a systemic response.…”
Section: Introductionmentioning
confidence: 99%
“…There was strong evidence that MJ moves in both phloem and xylem. Methyl jasmonate moves in tobacco phloem along with photoassimilates, and due to exchange between phloem and xylem is able to move in xylem as well (Thorpe et al 2007). In contrast, it was reported that jasmonic acid does not exchange between phloem and xylem, probably due to its chemical properties (Zhang and Baldwin 1997).…”
Section: Resultsmentioning
confidence: 99%